Prospective associations between bullying victimisation, internalised stigma, and mental health in South African adolescents living with HIV - Boyes, Mark; Pantelic, Marija; Casale, Marisa; Toska, Elona; Newnham, Elizabeth; Cluver, Lucie (Elsevier, 2020)
Background:Adolescents living with HIV may be at elevated risk of psychological problems, which are correlated with negative health outcomes. In cross-sectional research with HIV-affected adolescents, bullying victimisation and internalised HIV stigma have been associated with poorer psychological health. We extended these findings and tested longitudinal associations between bullying victimisation, internalised stigma, and mental health among adolescents living with HIV. We also tested whether relationships between bullying victimisation and psychological symptoms were mediated by internalised stigma.